The poetics of DNA - Roof, Judith, 1951- (Posthumanities, 2007)
In The Poetics of DNA, Judith Roof examines the rise of this powerful symbol and the implications of its ascendancy for the ways we thinkabout ourselves, about one another, and about the universe. A hyperbolized notion of DNA has become a vector, Roof argues, through which older ways of thinking can merge with the new, advancing long-discredited and insidious ideas.